1914
DOI: 10.5962/bhl.title.1655
|View full text |Cite
|
Sign up to set email alerts
|

American boletes

Abstract: Pileus yellow to brown. Sporophore large; stipe i cm. or more thick. Context decidedly bitter. i. T.felleus. Context not bitter. 2. T. indecisus. Sporophore usually small; stipe about 5 mm. thick, never reticulate. 3-T. gracilis. Pileus black or blackish; tubes becoming blackish when wounded. 4. T. alboater. i. TYLOPILUS FELLEUS (Bull.) P. Karst. Pileus thick, convex, usually 8-15 cm. broad, sometimes reaching a diameter of over 40 cm.; surface smooth, glabrous, variable in color, usually some shade of tan or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Another species that is similar to E. permagnificus is Boletus weberi Singer, which appears to be conspecific with Boletus pseudofrostii B. Ortiz, based on our phylogenetic reconstruction. This taxon belongs to another genus (see below) and differs by the smaller size (pileus up to 6.5 cm diam., stipe up to 5.3 × 1.7 cm), unchanging tissues on bruising, white basal mycelium, slightly smaller and shorter basidiospores (8.1-10.7 × 4.1-5.5 µm, Q m = 2.0), slightly narrower basidia (33-45 × 7-10 µm), smaller cheilocystidia (14-60 × 4-8 µm) and caulocystidia (14-29 × 8-9 µm), cylindrical, narrower pileipellis terminal cells (up to 10 µm wide) and the occurrence in Pinus-dominated or in mixed forests with Fagaceae in North (Atlantic and Gulf Coasts of the USA) and Central America (Belize) [28,[126][127][128][137][138][139][140].…”
Section: Taxonomymentioning
confidence: 99%
See 2 more Smart Citations
“…Another species that is similar to E. permagnificus is Boletus weberi Singer, which appears to be conspecific with Boletus pseudofrostii B. Ortiz, based on our phylogenetic reconstruction. This taxon belongs to another genus (see below) and differs by the smaller size (pileus up to 6.5 cm diam., stipe up to 5.3 × 1.7 cm), unchanging tissues on bruising, white basal mycelium, slightly smaller and shorter basidiospores (8.1-10.7 × 4.1-5.5 µm, Q m = 2.0), slightly narrower basidia (33-45 × 7-10 µm), smaller cheilocystidia (14-60 × 4-8 µm) and caulocystidia (14-29 × 8-9 µm), cylindrical, narrower pileipellis terminal cells (up to 10 µm wide) and the occurrence in Pinus-dominated or in mixed forests with Fagaceae in North (Atlantic and Gulf Coasts of the USA) and Central America (Belize) [28,[126][127][128][137][138][139][140].…”
Section: Taxonomymentioning
confidence: 99%
“…Figure 6A,B Selected morphological descriptions and illustrations: Murrill ([141], as "Suillellus luridus"? ; [137]), Singer [126,127], Both [128], Bessette et al [28,129,139,142], dubitatively García-Jiménez and Garza-Ocañas [143], Ortiz-Santana et al [138], García-Jiménez [144], García-Jiménez et al [145] and Gonzáles-Chicas et al [146].…”
Section: Taxonomymentioning
confidence: 99%
See 1 more Smart Citation
“…Research showed that As is absorbed by AMF hyphae (through RiPT and GiPT gene) [135,136], AMF reduces As(V) to As(III) (through RiarsC gene) [136], and finally, As is released through RiArsB, ATPase pump, and GiArsA into the soil [135,136]. It was shown that AMF can evaporate and methylate inorganic As through RiMT-11 into a wide range of organic As [134,137]; also, AMF causes more DMA release, especially when high concentrations of As(V) are present in the environment [134]. Numerous reports showed that coexistence with AMF has increased As evaporation and methylation as well as increased the As(III) to As(V) ratio in various crops, including rice and alfalfa [134,138,139].…”
Section: Arsenic (As)mentioning
confidence: 99%
“…[135,136]. It was shown that AMF can evaporate and methylate inorganic As through RiMT-11 into a wide range of organic As [134,137]; also, AMF causes more DMA release, especially when high concentrations of As(V) are present in the environment [134]. Numerous reports showed that coexistence with AMF has increased As evaporation and methylation as well as increased the As(III) to As(V) ratio in various crops, including rice and alfalfa [134,138,139].…”
Section: Arsenic (As)mentioning
confidence: 99%